Participatory process of developing performance indicators in a global partnership programme: the case of PROLINNOVA - Espineli, Marissa; Waters-Bayer, Ann (2005)
Programme monitoring and evaluation (M&E) presents a lot of challenges, especially when one adds to this process the dimensions of participation, partnership and learning. Then, the whole process becomes much more complicated. The PROLINNOVA M&E is a shared evolving process continuously sharpened to meet the needs of the partnership. This paper describes a specific part of that process, the development of performance indicators for the PROLINNOVA programme. The start-up process, already, has offered many insights in terms of creating a balance between the PROLINNOVA programme accountability and partners’ autonomy in decision-making and action. Side by side with creating shared ownership of the M&E system is the importance of the partners’ roles and responsibilities in making the system work.